2021
DOI: 10.18203/2394-6040.ijcmph20211202
|View full text |Cite
|
Sign up to set email alerts
|

Community perception and determinants of willingness to uptake COVID-19 vaccines among residents of Osun State, South-West Nigeria

Abstract: Background: Vaccine has been identified as the most cost-effective way of fighting COVID-19 pandemic. As most countries await the COVID-19 vaccine for mass administration amidst numerous misconceptions, it is imperative to assess willingness of the masses to take the vaccine. This study aimed to assess the determinants of willingness to uptake COVID-19 vaccines among residents of Osun State.Methods: A descriptive cross-sectional study design was employed. Seven hundred and forty-four respondents were enrolled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…This is similar to findings from a study conducted in Osun state in which a decline was noticed if payment will be required for the vaccine. 27 Our study also revealed that a greater percentage of the respondents who were willing to accept the vaccine expressed readiness to take as many doses as may be required. This contrasts with a study where people were not willing to take multiple doses.…”
Section: Discussionsupporting
confidence: 49%
“…This is similar to findings from a study conducted in Osun state in which a decline was noticed if payment will be required for the vaccine. 27 Our study also revealed that a greater percentage of the respondents who were willing to accept the vaccine expressed readiness to take as many doses as may be required. This contrasts with a study where people were not willing to take multiple doses.…”
Section: Discussionsupporting
confidence: 49%
“…The pooled vaccine Age was found to be a significant factor in accepting COVID-19 [9,14,20,22,[36][37][38]42]. Participants within the age of 24 and Good knowledge of COVID-19, belief that is beneficial [39,40,42] perceived contagiousness of the virus, and perceived threat to life [20,35] were also associated with COVID-19 vaccine acceptance.…”
Section: Resultsmentioning
confidence: 92%
“…Factors associated with COVID-19 vaccine hesitancy included age, [44] safety concerns, [12,22,23,26,41,42] unreliability of clinical trials, [12,22,37] doubt on efficacy and effectiveness of the vaccine, [23,28,37] fear of side effect, [9,12,15,23,27,28,36,37,40,41, 45] lack of confidence in the vaccine, [8] belief that the risk of getting COVID-19 is low, [15,24] disbelief in the existence of COVID-19, [15,24,26] mistrust in government and manufacturing companies, [12,24,26,45] cultural and religious disapproval [27,41]. Other factors include belief that immune status can combat the virus, [22] fear and dislike of injection, [11] infertility related myth, [26,27] electronic implant myth, [27] anti-vaccine message in social media, [33] and history of previous COVID-19 infection [45].…”
Section: Target Population Factors Affecting Acceptancementioning
confidence: 99%
“…In some local population studies 30 , 31 , willingness to receive a prospective vaccine was also associated with being a HCW.…”
Section: Discussionmentioning
confidence: 99%